A general numerical model for predicting the flexural behavior of hybrid FRP-steel reinforced concrete beams. (15th July 2021) - Zhou, Binbin; Wu, Ruoyang; Lu, Siqi; Yin, Shiping
Highlights: A numerical model to predict flexural behavior of hybrid RC beams was proposed. TCM was used to simplify the analysis of tension stiffening effect. LSM was developed to simplify the description of softening behavior of concrete. Simplified multilinear moment–curvature curve of hybrid RC beams was suggested. Abstract: Hybrid fiber reinforced polymer (FRP)-steel reinforced concrete (RC) beams exhibit different flexural failure modes with different reinforcement ratios and the contributions from tensile region and compressive region of the beams to flexural behavior vary accordingly. Therefore, a general model to predict the global nonlinear behavior of hybrid FRP-steel RC beams featured by common flexural failure modes is critical to analysis and design. In this paper, flexural behavior of a hybrid FRP-steel RC beam is considered as the systematic combination of mechanical behavior of FRP and steel RC tension chords and concrete strut. The Tension Chord Model (TCM) for steel and its extended application for FRP, properly considering the bond performance between FRP/steel reinforcement and the surrounding concrete, are employed to represent the tension stiffening effect in tensile region; the Linear Softening Model (LSM), incorporating the compressive fracture energy and considering the confinement effect, is applied to predict the softening behavior of compressive concrete. Based on the primary principles of equilibrium and compatibility, the aforementioned two models are assembled to numerically evaluate the advanced moment–curvature relationship and flexural behavior. Due to the proper combination and application of mechanical models, the global evaluation process is significantly simplified and avoids the lengthy iterative calculations performed in conventional numerical methods. Finally, the proposed calculational model is validated by comparisons between the predictions and experimental results of hybrid FRP-steel RC beams with common flexural failure modes available in the literature.